Association of HLA-DPB1 polymorphisms with rheumatoid arthritis: A systemic review and meta-analysis. (April 2018) - Jiang, Lu; Jiang, Dongdong; Han, Yao; Shi, Xian; Ren, Changle
Abstract: Background: The current reports on the association between HLA-DPB1 alleles and rheumatoid arthritis (RA) results were controversial. Thus, we conducted a meta-analysis to assess whether DPB1 alleles are associated with increased risk of rheumatoid arthritis. Methods: Systematic searches on PubMed, Embase, Elsevier, CNKI (China National Knowledge Infrastructure), Wanfang data and Cochrane Library prior to July 2017 were performed. The pooled odds ratios (ORs) and 95% confidence interval (95% CI) was used to assess the association between frequencies of DPB1 alleles and RA patients. Results: Eight studies with 592 cases and 935 controls were included in this meta-analysis. Overall, the pooled ORs showed that frequencies of DPB1*0401 and *0601 were higher in the RA group compared with controls (*0401: OR: 1.586, 95%CI: 1.296–1.941, P <0.001; *0601: OR: 1.921, 95%CI: 1.142–3.229, P =0.014). Whereas, the frequencies of DPB1*0101, *0402 and *0501 were lower in the RA control than the controls (*0101: OR: 0.691, 95%CI: 0.481–0.993, P =0.046; *0402: OR: 0.707, 95%CI: 0.555–0.902, P =0.005; *0501: OR: 0.502, 95%CI: 0.329–0.767, P =0.001). No associations were observed for DPB1*0201, *0202, *0301 and *0901 (*0201: OR: 1.129, 95%CI: 0.882–1.446, P  = 0.335; *0202: OR: 0.840, 95%CI: 0.940–1.441, P  = 0.527; *0301: OR: 0.769, 95%CI: 0.577–1.026, P  = 0.074; *0901: OR: 1.221, 95% CI: 0.541–2.755, P  = 0.630). Conclusions: This meta-analysis demonstrates that high frequency expression of DPB1*0401 and *0601 are significantly associated with susceptibility to RA, it may be a risk factor for occurrence of RA. Low frequency expression of DPB1*0101, *0402 and *0501 may be negatively associated with RA, it may be a protective factor for occurrence of RA. Highlights: The studies of HLA-DPB1 polymorphisms in rheumatoid arthritis(RA) still exist different arguments. High frequency expression of DPB1*0401 and *0601 may be a risk factor for occurrence of RA. Low frequency expression of DPB1*0101, *0402 and *0501 may be a protective factor for occurrence of RA. DPB1 alleles is a candidate novel predicted factor for RA patients.